2018
DOI: 10.1002/adbi.201700197
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Microfluidics‐Based Assisted Reproductive Technology: From Sperm Sorter to Reproductive System‐on‐a‐Chip

Abstract: The fields of assisted reproductive technology (ART) and in vitro fertilization (IVF) have progressed rapidly, yet still need further improvements. Microfluidic technology can incorporate various ART procedures such as embryo/gamete (sperm/oocyte) analysis, sorting, manipulation, culture, and monitoring. The introduction of paper‐based and droplet‐based microfluidics further improves the commercialization potential of this technology. The progress in 3D printing technology allows for the integration of microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 193 publications
(160 reference statements)
0
81
0
Order By: Relevance
“…Digital microfluidics is a state-of-the-art technique used to handle picoliter to microliter liquid droplets [166,167] using different mechanisms such as the Marangoni effect [168], magnetic fields [169,170], optical actuation [171] or electrostatic forces [172][173][174]. Recently, much attention has been given to the application of this format of microfluidics in various biomedical applications including assisted reproductive technology and in vitro fertilization [175]. It has been shown that the electrostatic fields used in digital microfluidic chips have negligible effects on cell viability, morphology [174,176] and gene expression [172], making such platforms suitable for both 2D [174,176,177] and 3D [172,173,178] cell culture.…”
Section: Digital Microfluidics In Spheroid Formation and Culturementioning
confidence: 99%
“…Digital microfluidics is a state-of-the-art technique used to handle picoliter to microliter liquid droplets [166,167] using different mechanisms such as the Marangoni effect [168], magnetic fields [169,170], optical actuation [171] or electrostatic forces [172][173][174]. Recently, much attention has been given to the application of this format of microfluidics in various biomedical applications including assisted reproductive technology and in vitro fertilization [175]. It has been shown that the electrostatic fields used in digital microfluidic chips have negligible effects on cell viability, morphology [174,176] and gene expression [172], making such platforms suitable for both 2D [174,176,177] and 3D [172,173,178] cell culture.…”
Section: Digital Microfluidics In Spheroid Formation and Culturementioning
confidence: 99%
“…As a science and technology, microfluidics can be used for various fluid mechanics applications, including slip flow in superhydrophobic microchannels [69,70] and drag reduction [71][72][73]. In parallel, microfluidic systems hold great promise for cell biology [74], assisted reproductive technology (ART) [75], drug delivery systems [76], anti-cancer drug screening [77] and disease modelling [78]. Recently, microfluidic platforms for spheroid formation and culture have been thoroughly reviewed by our group [13].…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Microchannels are basic components in drug delivery devices [1,2], micro-electro-mechanical-systems (MEMS) [3], and lab-on-a-chip systems [4], microfluidic assisted reproductive technology (ART) [5] and other microfluidic components [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Large surface-to-volume ratio (SVR) [21][22][23] of microchannels makes them an excellent choice for compact and efficient heat exchangers in electronic cooling devices [24,25].…”
Section: Introductionmentioning
confidence: 99%